Protecting the fabric of society? Heterosexual views on the usefulness of the anti-gay laws in Barbados, Guyana and Trinidad and Tobago. Issue 1 (2nd January 2017) - Jackman, Mahalia
Abstract: This study evaluated the extent to which people living in Barbados, Guyana and Trinidad and Tobago believe that the anti-gay laws currently in place: (1) reflect moral standards; (2) stop the spread of homosexuality; (3) are important from a public health perspective; and (4) protect young people from abuse. Analysis reveals that demographics, religion, interpersonal contact and beliefs about the origin of homosexuality all influenced an individual's views on the usefulness of the anti-gay laws in these states, but the significance of their impacts varied substantially across the arguments.